Decolonial readings with the liberation philosopher Enrique Dussel in comprehensive ecosophical and diatopic hermeneusis - Milagros Elena Rodríguez (Diálogos)
Decolonial readings with the philosopher of liberation Enrique Dussel in comprehensive hermeneutic ecoecophatic and diatopic, in the planetary decolonial project-complex emerge on stage presenting a dossier of Life and Legacy of Enrique Dussel. The Dialógos Magazine of the State University of Maringa, directed by Dr. Marco Cícero Cavallini, is dressed in a wonderful manner with the warm welcome from researchers who draw their feelings with their pen and tell how the works and example of the philosopher of liberation has touched us. Enjoy this hermeneusis that weaves together Dussel's legacy.